Why is Mortalin a Potential Therapeutic Target for Cancer? - Yoon, A-Rum; Wadhwa, Renu; Kaul, Sunil C; Yun, Chae-Ok (Frontiers in Cell and Developmental Biology, 2022)
Cancer is one of the leading causes of death worldwide, accounting for nearly 10 million deaths in 2020. Therefore, cancer therapy is a priority research field to explore the biology of the disease and identify novel targets for the development of better treatment strategies. Mortalin is a member of the heat shock 70 kDa protein family. It is enriched in several types of cancer and contributes to carcinogenesis in various ways, including inactivation of the tumor suppressor p53, deregulation of apoptosis, induction of epithelial–mesenchymal transition, and enhancement of cancer stemness. It has been studied extensively as a therapeutic target for cancer treatment, and several types of anti-mortalin molecules have been discovered that effectively suppress the tumor cell growth. In this review, we (i) provide a comprehensive sketch of the role of mortalin in tumor biology; (ii) discuss various anti-mortalin molecules, including natural compounds, synthetic small molecules, peptides, antibodies, and nucleic acids, that have shown potential for cancer treatment in laboratory studies; and (iii) provide future perspectives in cancer treatment.